PENGARUH CITRA MEREK CONVENIENCE STORE TERHADAP REPUTASI DI MATA KONSUMEN SELAKU PELAJAR SMA KRISTOFORUS 2 (Studi Komparasi antara 7-ELEVEN dengan LAWSON’S STATION Cabang Palem, Jakarta Barat) - Rustono Farady Marta (SEMIOTIKA: Jurnal Komunikasi, 2014)
Along the development era, in which human needs are no longer centered on SANDAG, food, and shelter, but it is rather the actualization needs and communication. In order to meet these needs, is now a place that has a convenience store concept started mushrooming in various parts of the world, especially in Indonesia. Two of the many convenience stores most visited Indonesian teenagers are 7-Eleven and Lawson's Station.This is a disturbing desire to continue the previous studies researchers entitled "Brand Image Research Lawson's Station Branch Lodan on Current Student Perceptions UBM 2013-2014 School Year". Current research is focusing on the comparison between the 7-Eleven brand and Lawson's Station, where both convenience stores open more outlets in the same area, namely in commercial Taman Palem, West Jakarta. In addition, the researchers borrowed glasses respondents same as the research sample, ie from among students of high school students Christopher II. It is taken that the results of this study are objective and can be generalized as the hallmark of a quantitative approach. A total of 82 students who are at least two (2) times a week visit to the convenience store were included as respondents of the total population of 457.This research aims to examine the influence of both the brand image of the store to the reputation in the eyes of high school students Christopher II as consumers, then compare the differences in effect. The results of the study there were differences between the 7-Eleven brand image with palm branches Lawson's Station, West Jakarta, obtained through comparison of regression equations. There is a difference of 0.521 which Lawson's reputation over 7-Eleven outperform reputation in the eyes of high school students Christopher 2. Keywords: Brand Image, Convinience Store, 7-Eleven, Lawson’s Station, Reputation, Kristoforus 2 Senior High School Students